Determination of tissue volume in 100% isodose for application with brachytherapy cylinder - Stefanovski, Zoran; Chakalaroski, Petar; Klisarovska, Violeta (My University, 2021)
Introduction: Among the minimum requirements for reporting gynecological brachytherapy treatment is the reporting of the size of the volume occupied by 100% isodose line (V100). This requirement also applies when a cylinder applicator is used to irradiate, most commonly, endometrial cancer. This volume is easily found from DVH plot. However, the total reported volume also includes the part of the volume occupied by the cylinder applicator. But we should report only tissue volume receiving at least 100% dose. This work describes the procedure for obtaining this volume and makes statistics to see what the deviations of the reported volume between different patients are. The most often clinically used cylinders were cylinders with diameters of 3.5 and 3 cm. The reference points at which the dose was normalized were at distances of 5 or 10 mm from the top of the applicator for the dose of 7 Gy. Materials and Methods: Treatment planning is carried out on the Varian BrachyVision treatment planning system. To determine only the volume of tissue covered by 100% isodose, it is necessary to set one side of the calculation grid to pass through the intersection of 100% isodose and the surface of the cylinder. When this is done, we can measure the distance from the top of the cylinder to the bottom edge of the grid. In this way we can calculate the volume of the cylinder that is enclosed by the 100% isodose curve. The difference in volume covered by 100% isodose surface and the volume of the calculated part of the cylinder gives the actual volume V100,t of tissue irradiated with at least 100% of the prescribed dose. Results and Discussion: For a cylinder with a diameter of 3.5 cm and a normalization point 5 mm from the top, the mean value of V100,t was 7.17 cm3 and the standard deviation was 2.84 cm3. For a cylinder with a diameter of 3 cm and a normalization point of 5 mm, the mean was 11.19 cm3 and the standard deviation was 6.18 cm3. For a cylinder with a diameter of 3.5 cm and a normalization point of 1 cm from the top, the mean value of V100,t was 26.53 cm3 and the standard deviation was 5.46 cm3 . For a cylinder with a diameter of 3 cm and a normalization point of 10 mm, the mean value was 26.76 cm3 and the standard deviation 4.38 cm3 . Comparison of confidence intervals suggests that in both cases the volume covered by 100% isodose originated in the same population (p=0.061). The volume of 100% isodose calculated for the whole grid, V100, in average is (3.65 +/- 1.26) times the V100,t for a 3.5 cm cylinder and (3.34 +/- 1.45) for a 3 cm cylinder.